Brachiopods of the Holm Dal Formation (late Middle Cambrian), central North Greenland - Zell, Mary G.; Rowell, Albert J. (Meddelelser om Grønland. Geoscience, 1988)
Brachiopods from the Holm Dai’l Formation are all inarticulates and some 70 percent belong to genera that had an intercontinental Cambrian distribution. The majority of the genera have relatively long stratigraphic ranges; because they are only moderately eurytopic, their chronostratigraphic resolution is modest. The species, however, are more strongly endemic than the genera and consist largely of forms that are known only from North Greenland or are referred to taxa whose distribution is limited to platforms around Cambrian Laurentia; only one species is known from another continent. The fauna consists of 14 species referred to 11 genera of which none of the latter are new. Six of the species are retained in open nomenclature because of limited material or inadequate information. Three of the species are new: Canthylotreta grada, Dactylotreta patriella, and Anabolotreta groenlandica